Transcription of microRNAs is regulated by developmental signaling pathways and transcription factors - Arnott, Malcolm; Sampilo, Nina Faye; Song, Jia L. (Frontiers in Cell and Developmental Biology, 2024)
In early embryonic development, the cross-regulation of transcription factors and signaling pathways are critical in mediating developmental and physiological processes. Additionally, many studies have shown the importance of post-transcriptional regulation of signaling and network components mediated by microRNAs (miRNAs); however, how miRNAs are transcriptionally regulated is poorly understood. miRNAs are critical fine-tuners of many biological processes and their dysregulation leads to a variety of diseases and developmental defects. Previously, we have shown that miRNAs are dynamically expressed throughout sea urchin development, suggesting that miRNAs are likely to be under transcriptional regulation.Here, we used pharmacological inhibitors, genetic constructs, and loss-of-function reagents to assess the impact of key signaling pathways (Wnt, Nodal, MAPK, Sonic Hedgehog, Delta/Notch, VEGF, and BMP) and transcription factors (Alx1, Ets1/2, and Tbr) on the transcript levels of the evolutionarily conserved miR-1, miR-31, miR-92 and miR-124; the invertebratespecific miR-71; and the echinoderm-specific miR-2002, miR-2007, and miR-2012. We also used computational methods to identify potential transcription factor binding sites of these miRNAs. Lists of binding motifs for transcription factors (TFs) were acquired from the MEME-Suite Motif Database and used as inputs for the algorithm FIMO (Find Individual Motif Occurrences), which detects short nucleotide motifs within larger sequences. Based on experimental data on miRNA expression in conjunction with bioinformatic predictions, we propose that the transcription factors Tbr, Alx1, and Ets1 regulate SpmiR-1, SpmiR-31, and SpmiR-71, respectively. We additionally observed significant effects on miRNA levels as a result of perturbations to Wnt, Nodal, MAPK, and Sonic Hedgehog signaling pathways, while no significant change on miRNA levels were observed with perturbations to Delta/Notch, VEGF, or BMP signaling pathways. Overall, this study provides insights into the transcriptional regulation of miRNAs by signaling pathways and transcription factors and contribute to our overall understanding of the genetic regulation of developmental processes.